Trivalent Rare Earth Complexes of Some Potential Antiinflammatory and Antipyretic Compounds. - BASAK, DEVASHISH (Asian Journal of Chemistry, 2010)
Binary complexes of 2-aminobenzoic acid (2-ABA), 3-aminobenzoic acid (3-ABA) and 4-aminobenzoic acid (4-ABA) with La(III), Pr(III), Nd(III), Sm(III) and Gd(III) have been studied paper electrophoretically at different temperatures and a constant ionic strength. The stability constants of the complexes have been reported.